Asean’s efforts and limitations on protecting migrant workers’ rights: in search of solutions through the lens of regulatory regionalism - Nguyen, Thuy Duong (Đại học Quốc gia Hà Nội, 2020)
The issue of migrant workers’ rights has been a difficult challenge for ASEAN to address. Many commentators pointed out the inadequacies of ASEAN’s governance on this issue, such as the lack of legally binding regional instruments which are compatible with international labour standards; the absence of an enforcement mechanism; the poor protection of migrant labourers’ rights in its member states. These shortcomings are the consequences of the “ASEAN way” approach which is based on the principles of sovereignty, non-interference on internal affairs and consensus on decision-making, combined with the incompatibility innational interests amongdifferent member states. However, it is unrealistic to expect that ASEAN would change these norms which are meant to guarantee the respect of member states’ sovereignty in order to improve the situation of migrant workers within the region. Hence, this paper focuses on the concept of regulatory regionalism as a possible solution for ASEAN to deal with this issue. Although it might be a long and challenging process, this innovative approach not only allows ASEAN to play a more central role, but also eases member states’ concern regarding their sovereignty. Accordingly, it would promote and protect the rights of migrant workers within the region in a truly comprehensive and integrated manner